2011
DOI: 10.1021/ac202047n
|View full text |Cite
|
Sign up to set email alerts
|

Development and Certification of a Standard Reference Material for Vitamin D Metabolites in Human Serum

Abstract: The National Institute of Standards and Technology (NIST), in collaboration with the National Institutes of Health’s Office of Dietary Supplements (NIH-ODS), has developed a Standard Reference Material (SRM) for the determination of 25-hydroxyvitamin D [25(OH)D] in serum. SRM 972 Vitamin D in Human Serum consists of four serum pools with different levels of vitamin D metabolites and has certified and reference values for 25(OH)D2, 25(OH)D3, and 3-epi-25(OH)D3. Value assignment of this SRM was accomplished usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 26 publications
0
81
1
Order By: Relevance
“…The HPLC system was calibrated with the Chromsystems Serum Calibration Standard D3/D3 nr 38033. To summarize, all LC-MS/MS and HPLC methods used were calibrated against either NIST SRM 2972 or commercially available calibrators (Chromsystems, Munich, Germany), traceable to NIST SRM 2972 (5,21). Calibration of the immunoassays Liaison 25 OH Vitamin D total (DiaSorin, Inc. Stillwater MN) and IDS-iSYS (Immunodiagnostic System, Boldon, UK) is traceable to UV spectrophotometry (26) and the assays were performed according to the manufacturers' instructions.…”
Section: Method-correlation Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The HPLC system was calibrated with the Chromsystems Serum Calibration Standard D3/D3 nr 38033. To summarize, all LC-MS/MS and HPLC methods used were calibrated against either NIST SRM 2972 or commercially available calibrators (Chromsystems, Munich, Germany), traceable to NIST SRM 2972 (5,21). Calibration of the immunoassays Liaison 25 OH Vitamin D total (DiaSorin, Inc. Stillwater MN) and IDS-iSYS (Immunodiagnostic System, Boldon, UK) is traceable to UV spectrophotometry (26) and the assays were performed according to the manufacturers' instructions.…”
Section: Method-correlation Studiesmentioning
confidence: 99%
“…An association of vitamin D status with cardiovascular diseases, cancer, and autoimmunity has been described (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Phinney et al [6] do not describe a new CRM but instead satisfy the novelty requirement by offering a significantly Bimproved^material. In 2012 Phinney et al [7] reported the first serum-based CRM with values assigned for three vitamin D metabolites, i.e., 25-hydroxyvitamin D 2 2 , and high levels of 3-epi-25(OH)D 3 , which must be chromatographically separated from 25(OH)D 3 for accurate measurement of total 25(OH)D. To achieve target levels, the normal level was diluted with horse serum, which contains no 25(OH)D, to provide a low level, and the remaining two levels were fortified with either 25(OH)D 2 or 3-epi-25(OH)D 3 . Even though SRM 972 was widely used, a major criticism was that the use of modified serum and/or the presence of non-endogenous metabolites in three of the four levels produced inaccurate results using some assays, particularly immunoassays.…”
Section: Novel Matrix Crmsmentioning
confidence: 99%